Kaedah pengajaran berkesan : Antara keperluan pelajar dan realiti pengajaran pengajian jarak jauh - Intan Safinas Mohd Ariff Albakri; Fazilah Idris; Maznah Ibrahium; Alawiah Ibrahim (Universiti Kebangsaan Malaysia, 2001)
The Distance Learning program of Universiti Kebangsaan Malaysia has successfully produced graduates from multiple disciplines since it was established in 1994. The program’s establishment has given a great number of individuals, who are working, the opportunity to pursue their studies at a higher level. The Distance Learning program emphasized on two most important components that are teaching and learning. Therefore, this research is conducted to gather the students’ perspectives on the effective teaching techniques used by lecturers teaching the program. 158 respondents who are the Distance Learning program’s students studying in Bangi campus participated in answering the questionnaire. Besides that, this research also focuses on identifying the popular techniques used by the lecturers and its relationship with the effective teaching techniques highlighted by the students. Last but not least, this research also discusses the relationship between ethnicity and the outlined teaching techniques